ANALISIS POLA KOMUNIKASI ORGANISASI PADA RAPAT KONFERENSI VIDEO DI PT MANDALA MULTIFANANCE TBK - Hendry Putra; Silvina Mayasari; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
In an organization, a process of exchanging information, ideas, feelings, and perspectives among individuals or groups is required to achieve a desired goal. In the modern era, the delivery of both verbal and non-verbal information is made easier by communication technology. These media act as an intermediary or a tool used to convey messages from a communicator to a recipient. Communication media can be virtual or physical and can include written, verbal, or non-verbal elements. They play a crucial role in daily life, such as in the process of delivering messages or information. The process of delivering information, supported by communication technology, will proceed more smoothly and successfully. One example is the use of a video conferencing application to coordinate work within a national company that has branch offices and thousands of employees spread across Indonesia. This type of research is descriptive qualitative research, which selects employees of PT Mandala Multifinance as sample informants. These informants hold the role of a leader in the marketing division and are responsible for delivering messages or information to guide a project for creating designs and videos for the branches. This is to ensure that the information and instructions conveyed to all branch offices achieve the intended purpose and desired goals. This is done with the support of the Teams application, allowing for direct, online, face-to-face meetings with representatives from Mandala Multifinance branches across Indonesia. By analyzing these online video conference meetings, the communication process and patterns used in the meetings can be concluded. Furthermore, data is collected using instruments in the form of observation, documentation, and in-depth interviews with the informants.